An implementation manual for an interprofessional enhanced recovery after surgery protocol in cardiac surgery following international established frameworks - Schmid, M. E.; Dolata, L.; König, H.; Stock, S.; Klotz, S. G. R.; Girdauskas, E. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Enhanced Recovery After Surgery (ERAS) protocols represent a paradigm shift in perioperative care, aim to optimize patient outcomes and accelerate recovery. This manual presents findings from implementing the INCREASE study, a bicentric prospective randomized controlled trial focusing on ERAS in minimally invasive heart valve surgery. Methods Utilizing the Consolidated Framework for Implementation Research (CFIR) and the Template for Intervention Description and Replication (TIDieR), the study examined contextual factors, intervention components, and implementation strategies. Results Key findings from the CFIR analysis revealed critical domains influencing implementation success. These included innovation characteristics, external and internal settings, and individual dynamics. The study showcased ERAS's adaptability to diverse healthcare systems, emphasizing its potential for successful integration across varying contexts. Furthermore, the importance of interprofessional collaboration emerged as a foundation of practical implementation, fostering teamwork, communication, and patient-centered care. Utilizing the TIDieR framework, this manual comprehensively describes ERAS intervention components, detailing preoperative counseling, intraoperative management, and postoperative care strategies. The manual underscored the importance of tailored, patient-centered approaches, highlighting the role of an academic ERAS nurse, early mobilization, and psychosomatic interventions in promoting optimal recovery outcomes. Discussion In conclusion, the INCREASE study provided valuable insights for creating an implementation manual for ERAS in cardiac surgery, emphasizing adaptability, collaboration, and ongoing evaluation as key drivers of successful implementation. These findings have broad implications for improving patient care outcomes and advancing perioperative practices in cardiac surgery settings.